Asuhan Keperawatan Keluarga pada Tn. A dengan Diabetes Melitus di Desa Kalibuntu RT 02 RW 02 Kecamatan Losari Kabupaten Berebes - Ikbal Kanebi; Ahmad Zakiudin; Anna Maulina Lestari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disease that often occurs in the elderly, characterized by hyperglycemia due to impaired insulin secretion or action. This research focuses on family nursing care for Mr. A, a DM sufferer, in Kalibuntu Village, Losari District, Brebes Regency. Based on data, the prevalence of diabetes in Indonesia is very high, with Indonesia ranking third in Southeast Asia. In Brebes Regency, the prevalence of DM is also significant, requiring special attention in management. The Friedman model is used in family nursing care, which emphasizes the role of the family in supporting the patient's health management. The care process includes assessment, diagnosis, planning, implementation, and evaluation. The assessment is carried out by collecting family data using clear and simple language. Nursing diagnoses are established based on data analysis, while nursing interventions are designed to meet the patient's specific needs. Implementation is carried out by carrying out the plans that have been prepared, followed by ongoing evaluation to assess the effectiveness of the intervention and make necessary adjustments. Management of DM in Mr. A involves five main pillars: education, meal planning, physical exercise, pharmacological interventions, and blood sugar checks. A positive attitude towards treatment plays an important role in achieving good glucose control and improving quality of life. These findings emphasize the importance of family involvement in DM care to ensure effective and sustainable management.